(untitled) (The Research of Medical Science Review, 2025)
Background: Non-Alcoholic Fatty Liver Disease (NAFLD) is a growing global health concern and is increasingly being observed ‘in individuals with Type 2 Diabetes Mellitus (T2DM)’ even in the absence of obesity. This association poses a risk for progression to more serious liver complications including fibrosis, cirrhosis, and hepatocellular carcinoma. To determine the frequency of NAFLD among non-obese patients diagnosed with Type 2 Diabetes Mellitus. Methods: A cross-sectional study was carried out in the Department of General Medicine at a tertiary care hospital. A total of 260 non-obese individuals aged 25–70 years with T2DM were enrolled using consecutive non-probability sampling. Participants were assessed through clinical evaluation and imaging or histological evidence of hepatic steatosis. Relevant sociodemographic and clinical data were recorded and analyzed using SPSS version 23. Chi-square test was applied, with a p-value ≤ 0.05 considered significant. Results: Out of 260 non-obese T2DM patients, 58.1% were diagnosed with NAFLD. Significant associations were found between NAFLD and factors ‘such as age, male gender, higher-normal BMI, longer diabetes duration, hypertension, and smoking’. Other sociodemographic factors showed no significant relationship. Conclusion: NAFLD is highly prevalent among non-obese individuals with T2DM. Routine screening for NAFLD in all diabetic patients, regardless of body weight, is recommended to enable early intervention and prevent complications.